Therapeutic potential of 4-substituted coumarins: A conspectus - Sharma, Manmohan; Vyas, Vivek K.; Bhatt, Shaival; Ghate, Manjunath D. (European journal of medicinal chemistry reports, 2022)
Substituted coumarins are a very large family of naturally occurring compounds, and substituted coumarins are versatile scaffolds for the development of medicinally active compounds. Coumarins are extensively found in higher plant families such as Rutaceae and Umbelliferae, and are ingredients in various essential oils such as cinnamon bark oil, cassia leaf oil, and lavender oil. Coumarin-based compounds are obtained from nature and substituted coumarins synthesized by chemists demonstrate antitumor, antibacterial, antifungal, anticancer, anticoagulant, antimalarial, antiviral, anti-HIV and anti-inflammatory activities. They are also used as fluorescent dyes and probes and possess a variety of other bioactive properties. Coumarin and its derivatives might have diverse mechanisms of action on different targets for different activities depending on the substitution pattern on the coumarin scaffold. The important progress of natural and synthetic 4-substituted coumarin derivatives that are biologically active against many diseases is the subject of this review study. The research for more potent molecules begins with the substitution of the coumarin scaffold on the C-4 position, which showed anticancer activity against A549, ACHN, H727, MCF-7, and HL60 cancer cell lines. Overall, the expansion of anticancer, antibacterial, and antimalarial agents is covered by substitution at the C-4 position of the coumarin scaffold. This comprehensive study could aid in the development of more strong drug candidates for numerous diseases in the future, with broad and fascinating therapeutic applications. [Display omitted]